(untitled) (Biological Sciences - PJSIR, 2011)
The branchipod Moina micrura was mass cultured using three different concentrations (250 ppm, 500 ppm, and 1000 ppm) of chicken manure in the medium for 21 days. In the first concentration (250 ppm), the maximum density (1694.44 ± 9.68) of M. micrura was obtained on the 9th day of inoculation and the number of plankton declined gradually afterwards. In the second concentration (500 ppm), the maximum density (7296.88 ± 54.35) appeared on the 11th day while in the third concentration (1000 ppm), the maximum density (1510 ± 15.27) was obtained on the 14th day of inoculation. Temperature range of 27-31 °C and pH of 6-7 was conducive for optimal growth of M. micrura.